STRUKTUR KOMUNITAS KUPU-KUPU (ORDO: LEPIDOPTERA) DI KOTA PALEMBANG SEBAGAI SUMBANGAN MATERI PADA MATA KULIAH ENTOMOLOGI - Riyanto Riyanto; Mgs. M.Tibrani; Yunilda Rosa (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
Butterflies are useful as consumers in the food chain, bioindicators, pollinators and animal food. The purpose of writing this article is to inform the structure of the butterfly community in Palembang as a material contribution to the Entomology course. The location of this research includes residential areas, shops, offices, terminals and stadiums in Palembang. The location of the butterfly sample is determined by purposive sampling. The collection of butterfly samples was carried out with roaming techniques as much as 4 times per location. The results of the study found 5 families of butterflies in Palembang. The highest to lowest percentage of families were Nymphalidae (45.7%), Pieridae (24.0%), Hesperiidae (11.6%), Lycaenidae (9.3%) and Papilionidae (9.3%). The highest percentage of individuals was found in the Jakabaring stadium (42%) followed by Bomm Baru offices (39%), Musi 2 housing (11%), Plaju shops (8%) and Karyajaya terminal (0%). The family Pieridae is found in two locations, namely Boom Baru offices (35.29%) and Musi 2 housing (57.14%). The Nymphalidae families are found in Jakabaring stadium (60%), Plaju shops (60%) and Musi 2 housing 42.82%). The conclusion that the structure of the butterfly community in Palembang found 129 butterfly individuals, 23 species and 5 butterfly families. The highest percentage of butterfly families in Palembang is Nymphalidae and the lowest is Lycaenidae and Papilionidae. The locations where the number of individuals and the number of butterfly families are the Jakabaring stadium and the Boom Baru offices.